Establishment and Maintenance of Brassica Alba and Solanum Lycopersicum on Hydroponic Culture at Laboratory Condition (Journal of Bio-Science, 2023)
Hydroponics culture offers immense benefits in plant research, making it a valuable and versatile tool in scientific investigations across plant biology, agronomy, horticulture and diverse fields of research. The present study has been carried out for the establishment of Brassica alba and Solanum lycopersicum on hydroponic culture in laboratory condition. Firstly, an ideal concentration of macro and micro nutrients was developed for both B. alba and S. lycopersicum seedlings. After germination of both seeds, seedling was carefully monitored over a 15-day observation period on seedling tray. Then transfer of two-week-old seedlings to hydroponic media resulted in successful adaptation for both species. B. alba displayed slow initial growth but progressed significantly with robust development in the long run. In contrast, S. lycopersicum adapted quickly and exhibited continuous growth throughout the observation period. By week 4, both species had matured, with B. alba plants showing larger roots and stems and the onset of flowering. Both B. alba and S. lycopersicum seedlings displayed distinct growth patterns in hydroponic culture. These findings contribute valuable insights into the growth dynamics and viability of these two plant species in hydroponic systems, providing important information for optimizing cultivation practices and improving agricultural productivity.J. Bio-Sci. 31(1): 87-98, 2023